SSR analysis of the genomic DNA of perspective Uzbek hexaploid winter wheat varieties - A. T. Adylova; G. K. Norbekov; E. E. Khurshut; E. V. Nikitina; F. N. Kushanov (Вавиловский журнал генетики и селекции)
The objective of this study was to investigate the genetic diversity of hexaploid wheat varieties of Uzbekistan breeding using simple sequence repeat (SSR) markers. These varieties are adapted to local conditions, and can be considered as the most important supplier of genetic resources for cultivation in Uzbekistan and other countries. Microsatellite markers are now most widely used and effective classes of DNA markers for genotyping, certification and classification of plant varieties. In this paper, genotyping results of 32 hexaploid wheat domestic varieties using 144 microsatellite primer pairs are presented. Microsatellite primer pairs were chosen from literature data and 36 primer pairs (from 144) gave polymorphic well-reproducible PCR-fragments. The individual SSR spectra differing in number of amplicons were obtained for each variety. A total number of 141 alleles for 36 microsatellite loci were detected. The number of alleles per locus ranged from 2 to 6, the mean number of alleles per locus (Na) was 3 alleles. For the studied genotypes group the effective number of alleles (ne) characterizing the loci by the allele frequency, varied from 1.7 to 4.8, the mean number of alleles per locus was 2.8. The expected heterozygosity (He) ranged from 0 to 0.792, averaging 0.626, in studied wheat population. The amplified fragment sizes ranged from 93 to 552 bp. The polymorphic index content (PIC) ranged from 0 to 0.758. A dendrogram was constructed using the alleles set of microsatellite loci, reflecting the phylogenetic differences of the studied hexaploid wheat varieties. It showed that Uzbekistan breeding varieties are divided into two main clusters, which may be evidence of their common origin.  A genetic formula has been developed for each Uzbek wheat variety. It can be used for identification, certification of these varieties, as well as for the selection of parental pairs in the wheat breeding programs.